Extreme Programming Dalam Pembangunan Sistem Informasi Akuntansi Simpan Pinjam - Amalia, Putri; Fadillah, Sunia Maharani; Syamsiah, Nurfia Oktaviani; Arizona, Nanda Diaz (Akasia: Artikel Ilmiah Sistem Informasi Akuntansi, 2023)
KPN Ikhlas is a Civil Servant Cooperative that provides various services to its members, one of which is a savings and loan service. KPN Ikhlas membership is open to all permanent employees in the Regional Office of the Ministry of Religion of West Kalimantan Province which is located at Jalan Sutan Syahrir No. 12 Pontianak. Using the right system development method, namely the Extreme Programming (XP) method which can be used with small to medium sized teams, has the advantage of dealing with frequent changes, being able to adapt quickly to changing needs, and overcoming problems with change through fle ible designs and features. Constraints encountered in one of the data that is still offline. The data processing system is not fully computerized. The risk of miscalculation in savings and loan transactions. General journal reports are still recorded manually without structured arrangements based on the period. There are no special records for saving, borrowing, installments and taking transactions. Delays in the preparation and reports of financial withdrawals. Switching from a manual system to a computerized one will be safer and easier because the process of filling in data must be in accordance with standard forms that are made so that data is stored safely. This system is used to support ongoing data management and in making transaction reports to run quickly so as to minimize errors in inputting report data.